THE DYNAMICS OF THE CONSTITUTIONAL COURT'S DECISIONS ON THE AUTHORITY OF THE JUDICIAL COMMISSION IN PERFORMING SUPERVISION OF THE SUPREME JUDGES - Fauzi Iswahyudi (NOMOI Law Review, 2022)
The concept of the principle of checks and balances in the principle of state institutions is essentially carried out by equal state institutions, but the practice is very far from what it should be, even after the Constitutional Court Decision Number 005/PPU-IV/2006 which limits the Judicial Commission's supervision of Supreme Court justices, but until now KY as a temporary commission and institution still supervises the Supreme Court justices, even though the Court through its decision has explicitly stated that KY is not an actor of judicial power and also only as a supporting organ should not interfere with the Supreme Court's judicial authority, but in fact it is the Supreme Court judge who gave the acquittal in 2019 still reported to KY so that the authority contradicts the Constitutional Court Decision Number 005/PPU-IV/2006 which has been limited by the Constitutional Court whose decision is final and binding. The research method used is the normative legal research method. The results of the study show that the Constitutional Court which has interpreted the constitution related to the Judicial Commission has clearly provided legal findings regarding the principle of state institutions that supporting organs such as the Judicial Commission cannot supervise Supreme Court justices.